Peningkatan Mutu Pada Program Studi Magister Pendidikan Agama Islam UIN Ar-Raniry - Muhammad Sufri (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
This study discusses the roles and strategies implemented by the Postgraduate Islamic Religious Education (PAI) study program at UIN Ar-Raniry Banda Aceh in improving its educational quality and analyzing the opportunities and challenges in its implementation. This study is a qualitative approach that collects the data through interviews observation, and documentation. The results of this study indicate that the postgraduate PAI study program at UIN Ar-Raniry has made efforts and set two strategic programs in improving its educational quality. First, external strategic programs include cooperation with other universities, student exchanges, cooperation in research and publication of scientific papers, and the development of assisted villages. Second, internal strengthening programs include involving students in study program activities, providing quality lecturers, having proficient in the technology of study program activities, providing quality academic services for study programs, focusing on carrying out the vision and mission of study programs according to the strategic plan and socializing them to students, improving the quality of learning, implementing admission selection and strict graduation requirements, providing adequate facilities and infrastructure, and carrying out study program activities with reference to the accreditation form.